2017
DOI: 10.1111/scs.12385
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and attitudes of women regarding gynaecological cancer prevention in an urban area of Greece in financial crisis

Abstract: The current financial crisis has negatively affected the women's ability to afford gynaecological examinations. Therefore, it is necessary to inform the population about the necessity of preventive gynaecological examinations starting from school age and at the same time, health information and promotion campaigns should be launched at a national level.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 30 publications
2
3
0
Order By: Relevance
“…According to experts, sunscreen products are recognized as the first line of defence and primary protective measure against the detrimental consequences of radiation exposure ( Urasaki et al, 2016 ). Further, the findings of this study were in line with previous research in the same domain conducted among the Saudi population and worldwide ( Bryant et al, 2015 , Saridi et al, 2016 , Ugurlu et al, 2016 ).…”
Section: Discussionsupporting
confidence: 91%
“…According to experts, sunscreen products are recognized as the first line of defence and primary protective measure against the detrimental consequences of radiation exposure ( Urasaki et al, 2016 ). Further, the findings of this study were in line with previous research in the same domain conducted among the Saudi population and worldwide ( Bryant et al, 2015 , Saridi et al, 2016 , Ugurlu et al, 2016 ).…”
Section: Discussionsupporting
confidence: 91%
“…In another study, the authors showed that about 63% of students did not reapply sunscreen and only 3% admitted to applying it regularly (Almuqati et al, 2018). Other education studies conducted in the USA (Hobbs et al, 2014), Brazil (Urasaki et al, 2016) and Greece (Saridi et al, 2016) also had reported similar results. These results suggest that there is a general awareness among the participants of the importance of reapplying sunscreen, with a majority reapplying it every 8 hours or more frequently.…”
Section: Discussionsupporting
confidence: 65%
“…The scale consisted of 50 items based on a large literature review and clinical observations to determine the information of women on gynecologic cancer prevention (4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15). The content validity was assessed in order to determine whether the items in the draft scale were sufficient in terms of quality and quantity.…”
Section: 32gynecologic Cancer Prevention Information Scalementioning
confidence: 99%
“…Health professionals (nurses, midwives, doctors, etc.) have the responsibility of protecting and improving health, and reaching women who constitute a large group of the society (12)(13)(14)(15). Accordingly, the first thing that should be done is to determine the current knowledge levels of the women objectively.…”
Section: Introductionmentioning
confidence: 99%